Extending the memorable tourism experience model: a study of coffee tourism in Vietnam. Issue 6 (15th February 2021) - Chen, Li-Hsin; Wang, Mei-Jung Sebrina; Morrison, Alastair M.
Abstract : Purpose: Despite the increasing recognition of coffee tourism, there is limited research on the influence of memorable tourism experiences (MTEs) on coffee tourist behaviours. This investigation attempted to fill the gap in extending the MTE model by integrating travel motivations and expectation–confirmation theory (ECT). Design/methodology/approach: A mixed-method approach was employed. A survey questionnaire containing closed- and open-ended questions was used to obtain quantitative and qualitative information. Interviews with coffee shop owners were also conducted to obtain greater insight. Findings: Both the quantitative and qualitative findings confirmed that coffee tourists' revisit and word-of-mouth intentions were strongly influenced by satisfaction and MTEs, which were predicted by confirmation of expectations (CoEs) and travel motivations. Research limitations/implications: The findings confirmed that travel motivation is one of the most important precursors of MTEs. CoE was also determined to be a precursor of MTEs. MTEs had positive influences on satisfaction, word of mouth (WoM) and revisit intentions. Practical implications: The results offer insights by identifying vital factors linked to coffee tourist experiences and satisfaction, which will aid practitioners developing better marketing strategies. Originality/value: The memorable tourism experience scale has rarely been applied in food tourism and particularly in relation to coffee consumption. Moreover, this research is unique in investigating the relationships among motivations, CoE, MTEs, satisfaction and WoM and revisit intentions.